2009
DOI: 10.2353/ajpath.2009.090474
|View full text |Cite
|
Sign up to set email alerts
|

Gla-Rich Protein Is a Novel Vitamin K-Dependent Protein Present in Serum That Accumulates at Sites of Pathological Calcifications

Abstract: Mineralization of soft tissues is an abnormal process that occurs in any body tissue and can greatly increase morbidity and mortality. Vitamin K-dependent (VKD) proteins play a crucial role in these processes; matrix Gla protein is considered one of the most relevant physiological inhibitors of soft tissue calcification know to date. Several studies have suggested that other , still unknown , VKD proteins might also be involved in soft tissue calcification pathologies. We have recently identified in sturgeon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 43 publications
3
89
0
Order By: Relevance
“…This highly conserved protein may be involved in the negative control of osteogenic differentiation of osteochondrogenic precursor cells in peripheral zones of fetal cartilage and at the cartilagebone interface as well as in the early phase of chondrocyte differentiation [14,15]. More recently, the UCMA/GRP protein was suggested to directly influence mineral formation and to play a role in processes involving soft tissue mineralization and abnormal calcification in the vascular system [16]. Investigation for alternatively spliced transcripts of UCMA/GRP in mice led to the identification of 4 isoforms, two of them probably secreted and two others reported to form aggregates in a structure similar to aggresome, an organelle where aggregated proteins are stored or degraded by autophagy [17].…”
Section: Introductionmentioning
confidence: 99%
“…This highly conserved protein may be involved in the negative control of osteogenic differentiation of osteochondrogenic precursor cells in peripheral zones of fetal cartilage and at the cartilagebone interface as well as in the early phase of chondrocyte differentiation [14,15]. More recently, the UCMA/GRP protein was suggested to directly influence mineral formation and to play a role in processes involving soft tissue mineralization and abnormal calcification in the vascular system [16]. Investigation for alternatively spliced transcripts of UCMA/GRP in mice led to the identification of 4 isoforms, two of them probably secreted and two others reported to form aggregates in a structure similar to aggresome, an organelle where aggregated proteins are stored or degraded by autophagy [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a reduction in the functional (carboxylated) MGP, rather than the amount of total MGP, may increase risk of vascular calcification (7). In addition to MGP, other vitamin K-dependent proteins in cardiovascular tissue, such as the gla-rich protein, may also influence atherosclerosis progression (8).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with chronic kidney disease, GRP is highly accumulated at sites of medial calcification, where the protein can be detected both inside the smooth muscle cells and in the extracellular matrix, in contrast with its almost absence in noncalcified areas [82]. GRP has been identified in other soft-tissue calcifications, such as skin calcification in dermatomyositis with calcinosis, invasive ductal carcinoma samples that include microcalcifications, and pseudoxanthoma elasticum where GRP co-localizes with mineral deposits [82].…”
Section: Gla-rich Proteinmentioning
confidence: 98%